Optimisation of insulator design for improved electric field performance - Ahmad, Hairilasri (2015)
Insulators are the integral part of the power system. Among them polymeric insulators are essential for the better performance. Polymer insulators become popular due to various advantages offered such as light weight, ease of installation and lower cost. Despite numerous advantages offered, there are also some problems regarding the polymer insulators. One of the factors governing the electrical performance of polymeric insulator is characterized by its field distribution along their length. This thesis has been made to analyse insulator performance via their electric field distribution. By improving the electric field distribution, it will help in enhancing their long term performance of insulator. The COMSOL Multiphysics software has been employed to investigate the electric field stresss along the insulator‟s surface. . An 11kV of polymeric insulator in clean and dry condition is modelled for simulation. For electric field‟s optimisation purpose, three different techniques are used to investigate its distribution along the insulator‟s surface. The techniques employed are as follow: i) different configuration of metal end fittings design, ii) improve of insulator weather shed shape and iii) installation of corona ring at appropriate location. From the observation, all the techniques proposed have significant effect on electric field distributions. Simulation of insulator model has shown that the maximum value of electric field stress was found to be at the region of metal end fittings. After the application of all optimization techniques, the electric field stress performance of the proposed insulator is reduced by 83.97% to 9.643x104V/m from 6.015x105V/m at the beginning.